Evaluation of Autofluorescence in Identifying Parathyroid Glands by Measuring Parathyroid Hormone in Fine-Needle Biopsy Washings - Liu, Zhen; Ma, Run-sheng; Jia, Jun-li; Wang, Tao; Zuo, Dao-hong; Yin, De-tao (Frontiers in Endocrinology, 2022)
Background: Near-infrared autofluorescence imaging has potentially great value for assisting endocrine surgeons in identifying parathyroid glands and may dramatically change the surgical strategy of endocrine surgeons in thyroid surgery. This study is designed to objectively evaluate the role of near-infrared autofluorescence imaging in identifying parathyroid glands during thyroid surgery by measuring intraoperative parathyroid hormone in fine-needle aspiration biopsy washings. Methods: This study was conducted at a tertiary referral teaching hospital in China from February 2020 to June 2020. Patients undergoing total thyroidectomy with or without neck lymph node dissection were consecutively included. The surgeon used near-infrared autofluorescence imaging to identify parathyroid glands during thyroid surgery and confirmed suspicious parathyroid tissues by measuring their intraoperative parathyroid hormone. Nanocarbon was injected into the thyroid gland if the thyroid autofluorescence intensity was too strong. The sensitivity and accuracy of near-infrared autofluorescence imaging and vision for identifying parathyroid glands, and the difference in autofluorescence intensity in various tissues were the main outcomes. RESULTS: Overall, 238 patients completed the trial. Based on the pathological and intraoperative parathyroid hormone results, the sensitivity of near-infrared autofluorescence imaging for detecting parathyroid glands（568 of 596 parathyroid glands; 95.30%）was significantly higher than that of vision（517 of 596 parathyroid glands; 86.74%, P<.001). The accuracy of near-infrared autofluorescence imaging (764 of 841 tissues; 90.84%) was significantly higher than that of vision (567 of 841 tissues; 67.42%, P<.001) when the evaluations of certain tissues were inconsistent. There was a significant difference between the autofluorescence intensity of the parathyroid glands and that of the lymph nodes (74.19 ± 17.82 vs 33.97 ± 10.64, P<.001). CONCLUSION: The use of near-infrared autofluorescence imaging, along with intraoperative parathyroid hormone and nanocarbon for the identification of parathyroid glands in thyroid surgery may increase the number of confirmed parathyroid glands. Using near-infrared autofluorescence imaging can effectively distinguish lymph nodes and parathyroid glands during lymph node dissection.